Analisis Sentimen Masyarakat Terhadap Mainan Anak “Lato-Lato” Menggunakan Metode Support Vector Machine (Svm) Pada Media Sosial Youtube - Ahmad Roshid; Erizal, S.Kom., M.Kom.; Rahmi Imada, S.Kom., M.Kom. (Prosiding Seminar Nasional Teknoka, 2023)
Lato-lato is a children's toy that has gone viral in Indonesia. This children's toy is quite controversial in Indonesian society because this toy creates quite a noise when played but also has several positive impacts for children. The purpose of this research is to analyze the sentiment of Indonesian people towards lato-lato toys from video comments on YouTube social media. The processes carried out are data crawling, preprocessing, normalization, labeling, and SVM classification. After the SVM classification process with a linear kernel, an accuracy of 81% was obtained. For positive sentiment, the precision is 80%, recall 85% and f1-score 82%, for negative sentiment, the precision is 83%, recall 77% and f1-score 80%. From the results of the sentiment analysis, more Indonesians respond positively to lato-lato, which indicates that Indonesians see lato-lato as not a problem and there are many positive benefits from lato-lato.